Management of Saline Soil Using Organic Manure and Gypsum Fertilizer for Growing Sweet Gourd in Coastal Region of Bangladesh (Journal of the Bangladesh Agricultural University, 2024)
Salinity is a major threat for growing cucurbit vegetables in the coastal zone of Bangladesh. A consecutive two year experiment was conducted during Rabi season 2019 and 2020 at Taltali and Amtali upazila, respectively of Barguna district Bangladesh to find out whether organic manure amendment and gypsum fertilizer can reduce salinity related degradation of soil and increase sweet gourd yield in coastal region of Bangladesh There were six treatments having control (no amendment), gypsum fertilizer, cowdung, poultry manure and the combination of gypsum fertilizer with cowdung and poultry manure. The design of the experiment was randomized complete block design with four replications. Every plot received recommended rate of nitrogen, phosphorus and potash fertilizer. The text crop was sweet gourd. Organic amendment significantly increase fruit yield of sweet gourd in saline soil. The performance of poultry manure was better than cowdung. The poultry manure, and poultry manure plus gypsum fertilizer produced fruit yield of 29.1 and 38.1 t ha-1, which is 67 and 119% higher over control treatment, respectively. The gypsum application had positive effect on fruit yield when it is applied with poultry manure. Application of organic manure increase soil moisture content, and reduce soil pH and electrical conductivity. Organic amendment with poultry manure is therefore recommended for sustainable yield of sweet gourd in saline soil, and reduces salinity related land degradation in coastal region of Bangladesh.J Bangladesh Agril Univ 19(1): 1–7, 2021https://doi.org/10.5455/JBAU.124573